EDUCATIONAL PARADIGMS IN AESTHETIC EDUCATION CLUSTER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article talks about the history of the emergence of the science of aesthetics and aesthetic education, aesthetic education and its cluster, as well as the opinions of philosophers and scientists and educational paradigms.